There is nothing for you here : finding opportunity in the twenty-first century - Hill, Fiona, 1965- (Boston, Massachusetts : Mariner Books, an imprint of HarperCollinsPublishers, 2021)
Foreign policy expert and key impeachment witness Fiona Hill reveals how declining opportunity has set America on the grim path of modern Russia--and shows how we can return hope to our forgotten places. In this deeply personal account, she shares what she has learned, and explains that only by expanding opportunity can we save our democracy.
Includes bibliographical references and index.
Keywords: Hill, Fiona, -- 1965-; Opportunity -- Economic aspects -- United States -- 21st century; Opportunity -- Social aspects -- United States -- 21st century; Political culture -- United States -- 21st century; United States -- Economic conditions -- 21st century; United States -- Social conditions -- 21st century; Autobiographies